Dual-Specificity Phosphatase CDC25B Was Inhibited by Natural Product HB-21 Through Covalently Binding to the Active Site - Zhang, Shoude; Jia, Qiangqiang; Gao, Qiang; Fan, Xueru; Weng, Yuxin; Su, Zhanhai (Frontiers in Chemistry, 2018)
The Cysteine 473 in the enzyme’s active site of Cdc25B is catalytically essential for substrate activation. The most well-reported inhibitors of Cdc25 phosphatases, especially quinone type inhibitors, play the role through inducing irreversible oxidation of this cysteine. Herein, we identified a natural product HB-21 having sesquiterpene lactone skeleton that could irreversibly bind to the cys473 via forming covalent bond. This compound inhibited recombinant human Cdc25B phosphatase with IC50 value of 24.25 M. Molecular modeling predicted that HB-21 is not only covalently binds to the cys473 of Cdc25B but form six hydrogen bonds with residues at the active site. Moreover, HB-21 can dephosphorylate their nature substrate cyclin-dependent kinase (CDK1) and inhibit cell cycle progression. In summary, this is a new type inhibitor of Cdc25B with novel mechanism.